Immunogenicity of SARS-CoV-2 vaccines in patients with breast cancer. (August 2022) - Denault, Elyssa; Nakajima, Erika; Naranbhai, Vivek; Hutchinson, Jennifer A.; Mortensen, Lindsey; Neihoff, Elizabeth; Barabell, Caroline; Comander, Amy; Juric, Dejan; Kuter, Irene; Mulvey, Theresa; Peppercorn, Jeffrey; et al.
Purpose: To explore the immunogenicity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines in patients with breast cancer based on type of anticancer treatment. Methods: Patients with breast cancer had anti-spike antibody concentrations measured ⩾14 days after receiving a full SARS-CoV-2 vaccination series. The primary endpoint was IgA/G/M anti-spike antibody concentration. Multiple regression analysis was used to analyze log10 -transformed antibody titer concentrations. Results: Between 29 April and 20 July 2021, 233 patients with breast cancer were enrolled, of whom 212 were eligible for the current analysis. Patients who received mRNA-1273 (Moderna) had the highest antibody concentrations [geometric mean concentration (GMC) in log10 : 3.0 U/mL], compared to patients who received BNT162b2 (Pfizer) (GMC: 2.6 U/mL) (multiple regression adjusted p = 0.013) and Ad26.COV2.S (Johnson & Johnson/Janssen) (GMC: 2.6 U/mL) ( p = 0.071). Patients receiving cytotoxic therapy had a significantly lower antibody titer GMC (2.5 U/mL) compared to patients on no therapy or endocrine therapy alone (3.0 U/mL) ( p = 0.005). Patients on targeted therapies (GMC: 2.7 U/mL) also had a numerically lower GMC compared to patients not receiving therapy/on endocrine therapy alone, although this result was not significant ( p = 0.364). Among patients who received an additional dose of vaccine ( n = 31), 28 demonstrated an increased antibody response that ranged from 0.2 to >4.4 U/ mL. Conclusion: Most patients with breast cancer generate detectable anti-spike antibodies following SARS-CoV-2 vaccination, though systemic treatments and vaccine type impact level of response. Further studies are needed to better understand the clinical implications of different antibody levels, the effectiveness of additional SARS-CoV-2 vaccine doses, and the risk of breakthrough infections among patients with breast cancer.